Temperature changes in soil covered by black oat straw - Zwirtes, Anderson Luiz; Reinert, Dalvan José; Gubiani, Paulo Ivonir; Silva, Vanderlei Rodrigues da; Mulazzani, Rodrigo Pivoto; Somavilla, André (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the effect of different amounts of black oat (Avena strigosa) straw covering soil surface on soil temperature at different depths. The treatments consisted of 0, 3, 6, and 9 Mg ha-1 straw. Soil temperature was measured hourly by a thermocouple inserted at different depths (0, 5, 15, 30, and 50 cm) and was used to adjust an equation correlating the temperature of covered soil with that of bare soil. With the correlations, it was possible to observe a point value of temperature (inversion temperature of straw effect), below which the presence of straw acts positively on the maintenance of soil temperature and above which the presence of straw acts negatively on soil heating.